Individual Morality, Internal Control Of Fraud With Organization Ethical Culture As Moderation: Moralitas Individu, Pengendalian Internal Terhadap Fraud Dengan Budaya Etis Organisasi Sebagai Pemoderasi - Fityan Izza Noor Abidin; Sri Enggar Puji Handayani; Sarwenda Biduri (Universitas Muhammadiyah Sidoarjo, 2023)
This study explores the impact of individual morality and internal controls on fraud risk in the implementation of healthcare assurance by Indonesia's BPJS. It emphasizes the moderating role of organizational ethics. Using a quantitative approach and Partial Least Square (PLS) analysis, data was gathered via direct surveys from Rumah Sakit Umum Al-Islam H.M. Mawardi Krian employees. The results indicate that individual morality has a limited effect on fraud risk, with individual moral reasoning playing a key role in behavior. However, internal controls significantly mitigate fraud risk, aligning with the fraud triangle theory's principles. Surprisingly, organizational ethical culture weakens the link between individual morality and internal control in relation to fraud risk, as a strong ethical culture raises standards and influences employee conduct positively. In conclusion, the study highlights the importance of strengthening internal controls in healthcare institutions to enhance employee ethics and prevent fraud. Future research could extend this investigation to include manufacturing companies, broadening our understanding of factors mitigating fraud risk in BPJS healthcare assurance. Involving multiple healthcare institutions would enhance the generalizability of these findings. highlights : Individual moral reasoning levels do not significantly impact fraud risk in healthcare assurance implementation, emphasizing the complexity of ethical decision-making. Effective internal controls are crucial in mitigating fraudulent activities, aligning with the principles of the fraud triangle theory. Organizational ethical culture can either strengthen or weaken the relationship between individual morality and internal control, highlighting the role of corporate ethics in shaping employee behavior and reducing fraud risk. Keywords : Individual Morality, Internal Control, Organizational Ethics, Fraud Risk, Healthcare Assurance